Control of the Tsetse Fly - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Tsetse Biology and Ecology: Their Role in the Epidemiology and Control of Trypanosomosis. S G A Leak. December 1998. 592 pp. ISBN 0 85199 300 1 £65 / h 92.90 / US$120 Published by ILRI, Nairobi, Kenya Available from: CABI Publishing Wallingfo